Global Foot‐and‐Mouth Disease Research Update and Gap Analysis: 2 – Epidemiology, Wildlife and Economics. (June 2016) - Knight‐Jones, T. J. D.; Robinson, L.; Charleston, B.; Rodriguez, L. L.; Gay, C. G.; Sumption, K. J.; Vosloo, W.
Summary: We assessed knowledge gaps in foot‐and‐mouth disease (FMD) research, and in this study, we consider (i) epidemiology, (ii) wildlife and (iii) economics. The study took the form of a literature review (2011–2015) combined with research updates collected in 2014 from 33 institutes from across the world. Findings were used to identify priority areas for future FMD research. During 2011–2015, modelling studies were dominant in the broad field of epidemiology; however, continued efforts are required to develop robust models for use during outbreaks in FMD‐free countries, linking epidemiologic and economics models. More guidance is needed for both the evaluation and the setting of targets for vaccine coverage, population immunity and vaccine field efficacy. Similarly, methods for seroprevalence studies need to be improved to obtain more meaningful outputs that allow comparison across studies. To inform control programmes in endemic countries, field trials assessing the effectiveness of vaccination in extensive smallholder systems should be performed to determine whether FMD can be controlled with quality vaccines in settings where implementing effective biosecurity is challenging. Studies need to go beyond measuring only vaccine effects and should extend our knowledge of the impact of FMD and increase our understanding of how to maximize farmer participation in disease control. Where wildlife reservoirs of virus exist, particularly African Buffalo, we need to better understand when and under what circumstances transmission to domestic animals occurs in order to manage this risk appropriately, considering the impact of control measures on livelihoods and wildlife. For settings where FMD eradication is unfeasible, further ground testing of commodity‐based trade is recommended. A thorough review of global FMD control programmes, covering successes and failures, would be extremely valuable and could be used to guide other control programmes.